Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera) - Runyon, Justin B.; Robinson, Harold (Zootaxa, 2010)
The new micro-dolichopodid genus Hurleyella and two new species, H. cumberlandensis and H. brooksi are described from the Nearctic. Hurleyella resembles the subfamily Medeterinae in having the legs bare of major setae, a depressed posterior mesonotum, and concave dorsal postcranium, but the complex male genitalia is unlike the relatively simple structure of traditional Medeterinae (e.g., Medetera, Thrypyicus, Corindia, etc.). Until the relationship of Hurleyella to other genera can be determined, and the limits of dolichopodid subfamilies refined, it should be considered as incertae sedis.